Analysis of phase change material integration in retail display cabinets for energy management. (25th March 2021) - Ben-Abdallah, R.; Leducq, D.; Delahaye, A.; Fournaison, L.; Pateau, O.; Ballot-Miguet, B.; Hoang, H.M.
Highlights: Identify design improvements and optimized parameter ranges for PCM integration. Set point temperature decreases from −3 to −5 °C: 36% PCM charging time reduction. Up to 4 demand response periods of 2 h in a day for display cabinets with PCM. Excess energy from PV panels can be used to charge PCM during daytime. Maximal power demand reduces by 13% in scenario using both PCM and PV panels. Abstract: Nowadays, retail stores are highly interested in the application of strategies such as demand response (DR) in refrigerated display cabinets (turning off the cold machine during a certain time) to increase their flexibility in energy management and to facilitate the integration of renewable energy sources. One of the main concerns related to DR deployment is the product and air temperature increase inside the cabinets when the refrigeration machine is turned off. Thermal energy storage TES by phase change materials (PCM) has been demonstrated to be a solution to replace for a limited time the refrigeration unit and maintain the product at low temperature. However, the presence of PCM heat exchanger altered the air curtain performance as well as the thermal behaviour of the display cabinet. Successful integration of PCM needs implementing new cabinet design and operating conditions. Moreover, if this technology is applied for many display cabinets, management strategies need to be considered so that the PCM can be charged and discharged in suitable conditions. If renewable energy sources are available, energy management scenarios combining electrical sources (grid and renewable) and thermal energy storage (PCM) can be planned. The main objectives of the present work are, first, to identify improvement options and optimized parameter ranges that can request the PCM integration in the display cabinet; and second, to test different energy management scenarios at the scale of a supermarket. The study shows that by improving the perforation pattern of the rear duct channel and increasing the fan power, a more homogeneous product temperature distribution and better thermal behaviour of the cabinet are obtained. The effects of the operating conditions (ambient and setpoint temperatures) on thermal behavior, energy consumption and PCM charging/discharging time are analyzed by experimental investigations. A simulation tool was developed to evaluate the global efficiency of a supermarket equipped with PCM display cabinets. For different energy management scenarios, it evaluates the potential of this technology to support DR applications, reduce the electricity contract power of the retail and facilitate the utilization of renewable energy sources, photovoltaic (PV) solar panels in particular. PCM integration allows a reduction of maximal power demand by 8% in the scenario without PV panels and by 13% in the scenario with PV panels.